Rescue of mis-splicing of a common SLC26A4 mutant associated with sensorineural hearing loss by antisense oligonucleotides - Pengchao Feng; Zhijiao Xu; Jialin Chen; Meizhen Liu; Yu Zhao; Daqi Wang; Lei Han; Li Wang; Bo Wan; Xingshun Xu; Dali Li; Yilai Shu; et al. (Elsevier, 2022)
A wide spectrum of SLC26A4 mutations causes Pendred syndrome and enlarged vestibular aqueduct, both associated with sensorineural hearing loss (SNHL). A splice-site mutation, c.919-2A>G (A-2G), which is common in Asian populations, impairs the 3' splice site of intron 7, resulting in exon 8 skipping during pre-mRNA splicing and a subsequent frameshift that creates a premature termination codon in the following exon. Currently, there is no effective drug treatment for SHNL. For A-2G-triggered SNHL, molecules that correct mis-splicing of the mutant hold promise to treat the disease. Antisense oligonucleotides (ASOs) can promote exon inclusion when targeting specific splicing silencers. Here, we systematically screened a large number of ASOs in a minigene system and identified a few that markedly repressed exon 8 skipping. A lead ASO, which targets a heterogeneous nuclear ribonucleoprotein (hnRNP) A1/A2 intronic splicing silencer (ISS) in intron 8, promoted efficient exon 8 inclusion in cultured peripheral blood mononuclear cells derived from two homozygous patients. In a partially humanized Slc26a4 A-2G mouse model, two subcutaneous injections of the ASO at 160 mg/kg significantly rescued exon 8 splicing in the liver. Our results demonstrate that the ISS-targeting ASO has therapeutic potential to treat genetic hearing loss caused by the A-2G mutation in SLC26A4.